Attitude Toward Continue Medical Education and Professional Development of Emergency Medical Personnel – Cross-Sectional Study of Physicians and Nurses - Machitidze, Manana; Goshadze, Nona (European Scientific Journal, ESJ, 2023)
Aim: Postgraduate education systems for medical professionals are constantly developing worldwide. The study aims to assess the knowledge and attitude toward the importance of continuing medical education and professional development of emergency medical personnel. Methodology and Design: Quantitative method study was conducted among Georgia "GEO Hospitals" regional clinics' emergency medicine department physicians and nurses. Study design cross-sectional study. Results: The attitude towards the knowledge and training of the clinic staff is heterogeneous, regardless of their qualification, and knowledge background. In addition to basic education, motivation is important for improving knowledge. In addition, the contact method is essential in training emergency management and life-saving. Conclusion: Continuous medical staff education with effective methods is essential for improving the qualification of medical personnel. This leads to high-quality treatment, the clinic's reputation, reliability, and safe patient care.